Menstrual variation in the acute testosterone and cortisol response to laboratory stressors correlate with baseline testosterone fluctuations at a within- and between-person level - Cook, C. J.; Fourie, P.; Crewther, B. T. (Stress - The International Journal on the Biology of Stress, 2020)
Studies have compared HPA and HPG stress reactivity across the follicular and luteal phases to assess the menstrual impact of estradiol and progesterone fluctuations. Ovulatory shifts in baseline and stressor-induced testosterone among athletic women offers a new framework to explore these responses. Here we investigated menstrual variation in baseline testosterone as a predictor of the acute testosterone and cortisol response to laboratory stressors in female athletes. Using a semi-randomized crossover design, thirty athletic women completed a physical (4 × 6-second bike sprints) and psychological (5 × 2-min cognitive tests with social evaluation) stressor on day seven (D7), 14 (D14), and 21 (D21) of a menstrual cycle. Baseline fluctuations and acute changes in salivary testosterone and cortisol were measured. The D14 testosterone response to both stressors (13.7%) exceeded D7 (7.3%) and D21 (7.0%), whereas cortisol was less responsive on D14 (9.8%) than D7 (13.0%) and D21 (12.0%); all moderate to large effect size differences (p < 0.01). Baseline testosterone, which presented large individual and menstrual variation with a D14 peak, was significantly related (moderate correlations) to testosterone and cortisol stress reactivity on a between-person level. Both outcomes were related (weak correlations) to within-person fluctuations in baseline testosterone, but these effects were mediated by testing day. In conclusion, menstrual variation in baseline testosterone concentration correlated with testosterone and cortisol reactivity to a physical and psychological stressor. Thus, gradients of stressor-induced hormonal change showed some dependency to endogenous testosterone, both individual differences and fluctuations over time, among naturally cycling athletic women.